PEMBERIAN INFORMASI NEONATAL DEVELOPMENTAL CARE MENINGKATKAN SIKAP PERAWAT DALAM MERAWAT BBLR - Yugistyowati, Anafrin; Endriyani, Lia (Journal of Holistic Nursing Science, 2018)
Newborn with low birth weight (LBW) in Indonesia is relatively high even up to 16,9 %. The role of the neonatal nurse is highly expected to provide care for newborn babies with LBW by giving supportive environment. Neonatal Developmental Care (NDC) is one of intervention that aims to implement modifications to the nursery environment and care practices to promote growth and development of newborn with LBW. Most of nurses still have no information related NDC and its implementation in neonatal room. This study aimed to explore the influence of NDC information exposure toward nurse’s attitude. A quasi-experimental with before-and-after design was applied. This study recruited 21 nurses to participate as intervention and control group. The Paired T-Test was performed to analyze the data. The results showed there is an influence of NDC information exposure toward nurse’s attitude in caring for newborn with low birth weight by P-value 0,00. This study recommend that NDC can be one of nursing intervention for caring newborn baby with LBW in order to optimize caring for infant along caring for growth and development during their treatment in hospital.